Sheanut Vitellaria paradoxa cake as ingredient in the diet of West African Dwarf Sheep Capra ovis - Ahaotu E. Obioha (Aceh Journal of Animal Science, 2018)
The aim of the study was to determine the effect of different levels of SNC on feed intake, digestibility and growth in West African Dwarf sheep. Sheanut cake (SNC) is a waste product from the process of extracting shea butter from shea fruits. Sheanut cake (SNC) is a waste product from the process of extracting shea butter from shea fruits. Many authors have investigated the importance of this waste to the ruminant livestock production industry. Sheanut cake (SNC) contained 122.4 - 189.0 g kg-1 of crude protein, 123.0 - 175.0 g kg-1 ether extract, 92.3 g kg-1 ADF, 100.7 g kg-1 NDF, 41.6-53.0 g kg-1 ash, 75.0- 138.0 g kg-1 crude fibre, dry matter of 915.0 g kg-1 and a metabolizable energy of 7.12 MJ kg-1. SNC also contained anti-nutritional factors (ANFs) (tannins, saponins, and theobromine) that reduced its use at a higher inclusion level in the diet of sheep. Varying levels of Sheanut cake (11.5 - 30%) were included in the diet of sheep to observe its effect on the performance of WAD sheep. It was observed that above 25% inclusion, feed intake, digestibility and average daily growth rate were depressed. No negative effect was reported in the haematology and blood biochemistry of sheep when SNC was included in the diet up to 25%. It has been established from this study that SNC contains appreciable levels of nutrient especially protein. However, the optimum inclusion level in the diet of WAD sheep is 25% beyond which feed intake, digestibility and growth is depressed.